Implementasi Seni Tari dalam Perkembangan Motorik Kasar Anak Usia Dini di TK Al-Kausar Medan - Ramadhani, DindaAsri; Zein, Azizah; Sabila, Khairiyah; Lubis, Hilda Zahra (Fakultas Pendidikan, Universitas Sultan Muhammad Syafiuddin Sambas, 2024)
This research aims to explore the implementation of dance in the gross motor development of young children at the AL-KAUSAR Kindergarten in Medan. The research method used is a qualitative descriptive approach, with a focus on gross motor movements such as body balance, changes in movement speed, and coordination of body parts when dancing. Primary data was obtained through field observations, while secondary data came from books, journals and other relevant references. The results of the research show that dance learning at AL-KAUSAR Medan Kindergarten makes a positive contribution to children's gross motor development, with gymnastics and dance lessons integrated into the curriculum. The implementation of this dance art is carried out through demonstration methods and direct practice, allowing children to express creativity and develop various aspects of their development. It is hoped that the results of this research can provide valuable insight for educators and early childhood education practitioners in enriching children's learning experiences through the art of dance